2011
DOI: 10.1007/978-3-642-23629-7_76
|View full text |Cite
|
Sign up to set email alerts
|

3D Organ Motion Prediction for MR-Guided High Intensity Focused Ultrasound

Abstract: Abstract. MR-guided High Intensity Focused Ultrasound is an emerging non-invasive technique capable of depositing sharply localised energy deep within the body, without affecting the surrounding tissues. This, however, implies exact knowledge of the target's position when treating mobile organs. In this paper we present an atlas-based prediction technique that trains an atlas from time-resolved 3D volumes using 4DMRI, capturing the full patient specific motion of the organ. Based on a breathing signal, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…implanted surrogate markers). In [3] a prediction error of 1.1 mm is achieved by acquiring 3D information of the patient specific liver motion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…implanted surrogate markers). In [3] a prediction error of 1.1 mm is achieved by acquiring 3D information of the patient specific liver motion.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the low sampling rate, the learning based algorithms would lead to considerable prediction errors at each ex-and inhalation position before adapting. Therefore we use a similar technique as proposed in [3], where a one-dimensional breathing model based on the measured pencil beam navigators is created. In contrast to the latter approach where the model is acquired in a training phase and then stays fixed, our respiratory model steadily grows even during increasing treatment time T .…”
Section: Temporal Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of the organ drift is difficult by using external sensors. Arnold et al [62] developed a statistical exhalation drift model. They reported that estimation with the drift model showed significant improvement compared to estimation without the drift model.…”
Section: Livermentioning
confidence: 99%
“…In minimally invasive surgery, the methods are mainly based on the use of intraoperative imaging and tracking systems [8][9][10]. One solution to the deformation produced by the movement of the organ was described by Zhang et al [11], who compensate organ motion using an electromagnetic tracking system.…”
Section: Mental Map and Navigationmentioning
confidence: 99%